Efficacy of Pharmacopuncture for Treating Children with Physical Disabilities in Uzbekistan - Ismailov N Zohidjon; Yu Jun-Sang (Korean Pharmacopuncture Institute, 2013)
Objective: This research was performed to investigate the efficacy of complex rehabilitation combined with pharmacopuncture treatment for the children with neuromotor system diseases. Methods: Fifty (50) patients aged from 5 to 15 yr old were compared. Twenty (20) patients received conventional treatments and complex rehabilitation as a control group, and fifty (50) patients received complex rehabilitation with pharmacopuncture. At their first visits, the patients had checkups and neurological scales, and after 10 days of pharmacopuncture treatments and 55 days of rehabilitation, they also took neurological scales. We studied the pre and post effects of the treatment group. Results: The number of patients with ankle joint disorder and contracture, knee joint contracture, steppage, horsey hoof, shoulder weakness and contracture, radio-carpal joint disorder and contracture, arm hypotrophia, arm atrophia, leg hypotrophia and total atrophia decreased after treatments. Conclusion: This study showed the efficacy of pharmacopuncture combined with complex rehabilitation for the treatment of neuromotor system diseases.